Glymphatic system dysfunction associated with cognitive impairment in chronic tinnitus patients - Du, Yinjuan; Huang, Zhichun; Wu, Yuanqing; Xue, Yuan; Che, Zigang (Frontiers in Neuroscience, 2024)
BackgroundThe glymphatic system has been regarded as a pivotal factor in the pathogenesis of neurodegenerative diseases. Given the heightened risk of cognitive impairment in chronic tinnitus patients, the possible alterations of the glymphatic system in tinnitus patients remain elusive. This study was designed to evaluate glymphatic dysfunction in chronic tinnitus patients using the diffusion tensor imaging (DTI) along the perivascular space (DTI-ALPS) approach.MethodsFifty chronic tinnitus patients and 50 age, sex, and education-matched healthy controls (HCs) with normal hearing thresholds were recruited. The DTI-ALPS was calculated from each group. We investigated the differences in the DTI-ALPS index between the tinnitus patients and HCs. The relationships between the DTI-ALPS index and specific cognitive performance were further assessed.ResultsThere were significant differences in the DTI-ALPS index between the two groups. The DTI-ALPS index was significantly lower in the tinnitus group than in HCs group (p < 0.01). In addition, the Dyyproj index was significantly higher in the tinnitus group than in the HC group (p < 0.01). In chronic tinnitus patients, the decreased DTI-ALPS index was negatively associated with worse TMT-B scores (r = −0.309, p = 0.039). Moreover, the increased Dyyproj index was negatively correlated with the reduced AVLT performances (r = −0.413, p = 0.005).ConclusionIn this current study, glymphatic system activity in chronic tinnitus was investigated for the first time using DTI-ALPS index. Significant decrease in glymphatic system function was detected in chronic tinnitus, which correlated well with the specific cognitive performance. The current study may provide pivotal imaging markers for chronic tinnitus with cognitive impairment.